Allergen immunotherapy for the prevention of allergic disease: protocol for a systematic review - Dhami, Sangeeta; Pfaar, Oliver (Pediatric allergy and immunology, 2016)
Background The European Academy of Allergy and Clinical Immunology (EAACI) is in the process of developing the EAACI Guidelines for Allergen Immunotherapy (AIT) for the Prevention of Allergic Disease. We seek to critically assess the effectiveness, cost-effectiveness, and safety of AIT in the prevention of allergic disease. Methods We will undertake a systematic review, which will involve searching international biomedical databases for published, in progress and unpublished evidence. Studies will be independently screened against pre-defined eligibility criteria and critically appraised using established instruments. Data will be descriptively and, if possible and appropriate, quantitatively synthesized. Discussion The findings from this review will be used to inform the development of recommendations for EAACI's Guidelines on AIT.
Gesehen am 03.05.2019
First published: 12 December 2015